2022
DOI: 10.1001/jamasurg.2022.4123
|View full text |Cite
|
Sign up to set email alerts
|

Same-Day Discharge After Minimally Invasive Colectomy

Abstract: This article describes elements of a same-day discharge program for minimally invasive colectomy as an evolution of enhanced recovery pathways for colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Several operative variations can further improve patient recovery by minimising operative trauma and pain, including intracorporeal versus extracorporeal anastomosis for laparoscopic right hemicolectomy [ 43 ]. Pfannenstiel specimen extraction versus midline specimen extraction [ 44 ], or natural orifice specimen extraction versus conventional transabdominal specimen extraction [ 45 , 46 ]. Individual surgeon expertise and experience are important factors [ 47 , 48 ], as well as proficiency with the surgical platforms used, including conventional laparoscopy, robotic surgery, or transanal approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Several operative variations can further improve patient recovery by minimising operative trauma and pain, including intracorporeal versus extracorporeal anastomosis for laparoscopic right hemicolectomy [ 43 ]. Pfannenstiel specimen extraction versus midline specimen extraction [ 44 ], or natural orifice specimen extraction versus conventional transabdominal specimen extraction [ 45 , 46 ]. Individual surgeon expertise and experience are important factors [ 47 , 48 ], as well as proficiency with the surgical platforms used, including conventional laparoscopy, robotic surgery, or transanal approaches.…”
Section: Discussionmentioning
confidence: 99%
“…1 Same-day discharge (SDD) pathways represent the evolution of ERPs by optimizing the elements of perioperative care that keep patients hospitalized after colorectal surgery. 2,3 After an initial series from France, studies from Canada and the United States have demonstrated its feasibility in different settings and with different modalities of postdischarge care. [4][5][6] The implementation of SDD protocols after colectomy requires a multifaceted approach, including advanced surgical techniques, opioid-sparing analgesia to promote return of bowel function, early remote follow-up methods, and patient-related factors.…”
Section: Limitaciones: Estudio Unicéntricomentioning
confidence: 99%
“…3 Many of the barriers to SDD implementation focus on the potential for SDD failure and/or early readmission, which may result in negative clinical and economic outcomes. 2 Identification of factors predictive of SDD success or failure may provide early "warning signs" for providers to keep patients hospitalized instead of discharged on the day of surgery, thus decreasing several of the barriers to SDD implementation by increasing the chances of success. Therefore, the primary objective of this study was to identify patient-related or perioperative factors that impact SDD success and failure.…”
Section: Limitaciones: Estudio Unicéntricomentioning
confidence: 99%
See 1 more Smart Citation
“…Along with a few other researchers, our group has previously published the results of our same day discharge (SDD) after minimally invasive colectomies. [4][5][6][7] Yet there is scant examination of postoperative opioid requirements in this specific population and how they affect outcomes such as readmissions. Older work in the past has identified early discharge as a significant risk factor for readmission.…”
mentioning
confidence: 99%